ON WEIGHTED CLASSES OF ENTIRE FUNCTIONS IN C^n - Petrosyan, A. I. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2006)
In the paper the weighted classes A_ω^2(C^n) t of entire functions of several complex variables are introduced. These classes depend on parameter-function ω(x) and they are arbitrarily large. For functions belonging to A_ω^2(C^n) the integral representation is obtained.